Estudio de factibilidad para el desarrollo turístico del río Quevedo - Rivera Cerezo, Teodoro Felipe (2012)
This work was held at the Canton Quevedo province Los Ríos, whose geographical location is 1 ° 3´18´´ of South latitude and 79 ° 25´24´´ of West longitude, at an altitude of 73 m, with duration of eight months, general objective was to establish a feasibility study for the development of tourism of the Quevedo River. The surveys were carried out 150 people between men and women divided equally between the 8 parishes of Quevedo. Later surveys were conducted in different neighborhoods located on the banks of the River. The results were: the high percentage of el 55.5% of quevedeños is according to a tourism development plan to make in this town, compared to 2% agree, reflects the need for project, therefore occur that the 46% of respondents say that there must be arrangements of streets for projecting Quevedo as a tourist potential. And on the other hand is worrying the percentage of the 40.5% of quevedeños that goes every fortnight to other tourist areas nearby such as spas and swimming pools of the manna and Valencia, which causes flow of money to other locations. Community project as tourist potential should be improved in some respects as e.g. 46 per cent of respondents were of the view that the arrangement of streets should improve. On the other hand 33.5% of respondents indicated that they would like to take the Quevedo River aquatic bicycles and 50.5% of them say that it should establish booths in tourist sites as an additional service, above indicates that the population required of tourist sites in Quevedo with all the services offered elsewhere. Similarly, it is important to emphasize that 49% of respondents would help with the development plan dealing well with tourists and 35.5 per cent of them would not throwing waste into the River.